Evaluation of subcutaneous and alveolar implantation surgical sites in the study of the biological properties of root-end filling endodontic materials - Luciano Tavares Angelo Cintra; Pedro Felício Estrada Bernabé; Ivaldo Gomes de Moraes; João Eduardo Gomes-Filho; Tetuo Okamoto; Alberto Consolaro; Tiago Novaes Pinheiro (University of São Paulo, 2010)
OBJECTIVE: The aim of this study was to compare two methodologies used in the evaluation of tissue response to root-end filling materials in rats. MATERIAL AND METHODS: Forty rats were divided into 4 groups: in Groups I and II (control groups), empty polyethylene tubes were implanted in the extraction site and in the subcutaneous tissue, respectively; in Groups III and IV, polyethylene tubes filled with ProRoot MTA were implanted in the extraction site and in the subcutaneous tissue, respectively. The animals were killed 7 and 30 days after tube implantation, and the hemi-maxillas and the capsular subcutaneous tissue, both with the tubes, were removed. Specimens were processed and evaluated histomorphologicaly under light microscopy. The scores obtained were analyzed statistically by the Kruskal-Wallis test (p<0.05). RESULTS: There were no statistically significant differences between the implantation methods (p=0.78033, p=0.72039). It was observed that the 30-day groups presented a more mature healing process due to smaller number of inflammatory cells. CONCLUSIONS: The present study showed no differences in tissue responses as far as the implantation site and the studied period were concerned. Alveolar socket implantation methodology represents an interesting method in the study of the biological properties of root-end filling endodontic materials due to the opportunity to evaluate bone tissue response.